2018
DOI: 10.1007/s11101-018-9592-y
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in extraction and analysis procedures of natural chlorogenic acids

Abstract: Chlorogenic acids (CQAs), the esters of caffeic and quinic acid, are biologically important phenolic compounds present in many plant species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 120 publications
6
87
0
Order By: Relevance
“…Chlorogenic acid was isolated from different plants species such as Etlingera elatior leaves, coffee, and fruit [27] as well as medicinal plants [17]. The chlorogenic acid is known for strong its anti-oxidant, anti-cancer, anti-inflammatory, and antiviral properties, and modulates the anti-oxidant enzyme activities [28,29]. Protocatechuic acid, sinapic acid and p-hydroxybenzoic acid were relatively low but they are considered to be important anti-oxidant and anti-cancer compounds [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Chlorogenic acid was isolated from different plants species such as Etlingera elatior leaves, coffee, and fruit [27] as well as medicinal plants [17]. The chlorogenic acid is known for strong its anti-oxidant, anti-cancer, anti-inflammatory, and antiviral properties, and modulates the anti-oxidant enzyme activities [28,29]. Protocatechuic acid, sinapic acid and p-hydroxybenzoic acid were relatively low but they are considered to be important anti-oxidant and anti-cancer compounds [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Four derivatives ( 10 , 18 , 21 , and 25 ) of chlorogenic acid were detected in VOP ( Table 3 , Figure 2 ). An interpretation of their MS 2 spectra using previously developed hierarchical keys enabled to assign these peaks to a particular positional derivative [ 38 , 39 , 40 ]. Furthermore, it was found that the fragment ion type and ion intensity were in a good correlation with the position of the caffeoyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Chlorogenic acids, mono‐ and dicaffeoyl esters of quinic acid have attracted the attention of the scientists because of their broad spectrum of biological activities and their health effects, such as antispasmodic, hepatoprotective and choleretic activities, antioxidant, antiviral, antibacterial, anticancer and anti‐inflammatory properties, and reduction of the relative risk of diabetes type 2 and Alzheimer's disease . These secondary metabolites are widely distributed in Plant Kingdom and particularly in the species of Asteraceae family …”
Section: Introductionmentioning
confidence: 92%